Share and take turns - Meiners, Cheri J., 1957- (Meiners, Cheri J., 1957- Learning to get along., 2003)
Explains what sharing means and provides examples of different ways that two people can share what they both want, such as taking turns, dividing things, or playing together. Includes information and extension activities for parents or teachers.